The Impact of the Covid-19 Pandemic on Tourist Visits in Central Java (Universitas Negeri Semarang, 2023)
In March 2020, the Covid-19 virus spread in Central Java and hit tourism in Central Java, where Central Java is the province with the most tourist attractions on the island of Java. This study aims to determine the impact of tourist visits, both foreign tourists and domestic tourists in Central Java during the Covid-19 pandemic and to see the policies issued by the Government that aims to protect Central Java tourism. The research method used in this study is descriptive quantitative where the independent variable is Covid-19 and the dependent variable is the number of visits by foreign tourists and domestic tourists. The results of this study indicate that the Covid-19 pandemic has a negative effect on foreign tourist visits and domestic tourist visits to Central Java. The number of foreign tourist visits during the pandemic, namely in 2020, the average number of foreign tourist arrivals decreased by 88.68 percent, while the number of domestic tourist visits in 2020 decreased by 60.91 percent.